Rethinking the European Social Market Economy: Introduction to the Special Issue. (9th December 2018) - Claassen, Rutger; Gerbrandy, Anna; Princen, Sebastiaan; Segers, Mathieu
Abstract: This contribution offers an introduction to the Special Issue 'Rethinking the European Social Market Economy'. It places the Special Issue against the background of the debate on free markets versus social protection in the European Union and the inclusion of the notion of 'social market economy' in the Treaty on European Union. It sketches the meaning and development of the social market economy concept, and introduces the key questions underlying this Special Issue and the contributions included in it.